Osteosarcomatous Divergence in Dedifferentiated Liposarcoma Presenting as a Colonic Mass - Jeenal Gordhandas; Grace Lin; Ann M. P. Tipps; Somaye Y. Zare (Case Reports in Pathology)
Dedifferentiated liposarcomas most commonly arise in the retroperitoneum, accounting for 10% of liposarcomas. Heterologous differentiation occurs in 5-10% of dedifferentiated liposarcomas; however, divergent osteosarcomatous differentiation is rare. We report a rare case of initial presentation of dedifferentiated liposarcoma with osteosarcomatous component as a colonic mass in a 72-year-old man. The tumor is mainly composed of bony trabeculae with intervening highly atypical cells and adjacent high-grade mesenchymal nonlipogenic tumor, as well as areas of well-differentiated liposarcoma. Immunohistochemical studies showed diffuse positivity for SATB2 in the atypical cells and fluorescence in situ hybridization revealed high-level amplification of MDM2 gene, supporting the diagnosis of well-differentiated and dedifferentiated liposarcoma with heterologous osteosarcomatous differentiation.